A Cyber Security And Protection Of Privacy Rights In E-Commerce Transactions - Helma Widya; Hermansyah Alam (Sean Institute, 2025)
The rapid growth of e-commerce has revolutionized the way businesses and consumers interact, providing convenience and accessibility. However, this advancement also presents significant challenges in cybersecurity and the protection of privacy rights. This paper examines the key cybersecurity threats in e-commerce transactions, including data breaches, identity theft, phishing attacks, and unauthorized access. It also explores the legal and regulatory frameworks designed to protect consumer privacy, such as GDPR, CCPA, and Indonesia’s Personal Data Protection Law. The study analyzes existing security measures, including encryption, multi-factor authentication, and blockchain technology, to enhance transaction security and safeguard user data. Additionally, the research highlights the role of businesses in ensuring compliance with privacy laws and implementing best practices in data protection. The findings suggest that while technological solutions play a crucial role in mitigating cybersecurity risks, consumer awareness and regulatory enforcement are equally important in strengthening e-commerce security.